A novel computer-based simulated learning environment in audiology with learning assistance: preliminary findings - Dzulkarnain, Ahmad Aidil Arafat; Rahmat, Sarah; Ismail, Ajune Wanis; Tengku Zam Zam, Tengku Zulaila Hasma; Musa, Ramli; Badzis, Mastura (Kulliyyah of Medicine, International Islamic University Malaysia, 2019)
Introduction This paper describes the development and the evaluation of a new Two-dimensional (2D) computer-based (CB) Simulated Learning Environment (SLE) software for routine audiology tests that comes with learning assistance for audiology students. The aim of the study was to serve as preliminary evaluation on the effectiveness of the new 2D CB SLE audiology software among audiology students. Materials and Methods The development process of the new 2D CB SLE includes, (i) the identification of common errors made by students in the audiology clinic, (ii) the development of five case simulations that include three routine audiology tests incorporating learning assistance derived from the errors commonly made by audiology students and, (iii) the development of 2D CB SLE from a technical perspective. A preliminary evaluation of the use of the 2D CB SLE software was conducted among twenty-six second-year undergraduate audiology students.